Market Orientation: Do University Student Experiences Matter? A Case Study Of Second Year University Students In Uganda - Omagor, Charles; Nakigudde, Racheal; Asingo, Angela (Journal of Business and Management Inaba, 2025)
Market orientation in the higher education sector is receiving growing scholarly attention. There are several studies which show that market orientation has positive outcomes for organization performance. However, there is a lack of evidence in studies examining the relationship of market orientation and university student experiences in general and in specific Uganda. Hence, this study. A qualitative approach was deemed appropriate for the study. A sample of nine students in their second year of study in the Faculty of Marketing and international Business was used. Personal in-depth interviews using structured open-ended questions were used to examine the variables under study. A qualitative data analysis was carried out which showed that market orientation has many associations with university student experiences. The main themes for market orientation were customer focus and functional orientation which are important in creating and sustaining student experiences. The results showed some lapses in the implementation of market orientation. The findings for the association between study variables were consistent with extant literature except in cases where the study returned mixed results. The main themes for student experiences revealed that self-motivation is very important, gossip can have negative outcomes on student experiences, and though the physical environment is important it had not been well attended to. Lastly, the influence of peers and participation in non-academic activities could have mixed effects.